Variable stretch reduces the pro-inflammatory response of alveolar epithelial cells - Rentzsch, Ines (PLoS One, 2017)
Mechanical ventilation has the potential to increase inflammation in both healthy and injured lungs. Several animal studies have shown that variable ventilation recruits the lungs and reduces inflammation. However, it is unclear which cellular mechanisms are involved in those findings. We hypothesized that variable stretch of LPS-stimulated alveolar epithelial cells (AECs) reduces the production of pro-inflammatory cytokines compared to non-variable stretch. AECs were subjected to non-variable or variable cyclic stretch (sinusoidal pattern), with and without LPS stimulation. The expression and release of interleukin-6, CXCL-2 and CCL-2 mRNA were analyzed after 4 hours. The phosphorylation of the MAPKs ERK1/2 and SAPK/JNK was determined by Western Blot analysis at 0, 15, 30, 45 and 60 min of cyclic stretch. In LPS-stimulated AECs, variable cyclic cell stretching led to reduced cytokine expression and release compared to non-variable cell stretching. Furthermore, the phosphorylation of the MAPK ERK1/2 was increased after 30 minutes in non-variable stretched AECs, whereas variable stretched cells demonstrated only the non-stretched level of phosphorylation. After the 4h period of cyclic cell stretch and inhibition of the ERK1/2, but not the SAPK/JNK, signaling pathway, the gene expression of investigated cytokines increased in variable stretched, and decreased in non-variable stretched AECs. We conclude that in LPS-stimulated AECs, variable stretch reduced the pro-inflammatory response compared to non-variable stretch. This effect was mediated by the ERK1/2 signaling pathway, and might partly explain the findings of reduced lung inflammation during mechanical ventilation modes that enhance breath-by-breath variability of the respiratory pattern.